Proportionality and the Experience of Punishment - Berger, Benjamin L. (Sentencing in Canada: essays in law, policy, and practice, 2020)
"Sentencing in Canada contains a unique collection of essays that explore all key aspects of sentencing. The contributors include leading academics, criminal law practitioners, and members of the judiciary, and many of the authors have extensive experience working in the areas of sentencing and parole. The volume is not simply a statement of the law — instead, the chapters explore the wider context in which sentencing and parole decisions are taken. The volume also incorporates findings from the latest empirical research into sentencing policy and practice in Canada, including important issues such as sentencing Indigenous persons. As Mr Justice Moldaver notes in his preface, the volume “will be useful to criminal law practitioners and, more generally, to all persons interested in sentencing.”" - hinterer Umschlagtext